The Effect of Make a Match Learning Model on Students Mathematics Learning Motivation - Wahyuni, Lisa; Rahmat, Tasnim; Rusdi, Rusdi; Aniswita, Aniswita (Pusdikra Publishing, 2024)
The low motivation of students' mathematics learning makes researchers want to know the effect of the Make a Match learning model on students' mathematics learning motivation. The type of research conducted was pre-experimental research with a one group pretest-posttest design. This research was conducted in a class that was selected by random sampling. From the results of data analysis, the average student pretest questionnaire results were obtained 124,45 while the average student posttest questionnaire results are 131,59. From the results of the calculation of the paired sample t-test at the real level ?=0,05 also obtained the value of tcount =5,14 and ttable =2,048. Because tcount > t table then reject H0 and accept H1 which means that students' mathematics learning motivation after applying the Make a Match learning model is better than students' mathematics learning motivation before applying the Make a Match learning model. From these results it can be concluded that there is an effect of the Make a Match learning model on students' mathematics learning motivation.